2022
DOI: 10.4103/ijdr.ijdr_426_19
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Loss and Oral Health-Related Quality of Life among Adult Dental Patients

Abstract: Background: Oral diseases seriously impair the quality of life (QoL) in a large number of individuals and they may affect various aspects of life. Aim: To determine the relationship between tooth loss and oral health-related quality of life (OHRQoL) among adult dental patients. Study Setting and Design: A cross-sectional study was carried out among 296 adult dental patients aged 35–44 years attending Departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
5
0
1
Order By: Relevance
“…In the present study, it was found that a greater number of natural teeth had a significant impact on improving the OHRQoL for elderly individuals, which is approved by the previous studies. 6,11,13,40 The loss of teeth can significantly impact a person's overall well-being, both physically and emotionally. Having more natural teeth allows for better food chewing, leading to healthier and more adequate nutrition in the elderly population, ultimately increasing their quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, it was found that a greater number of natural teeth had a significant impact on improving the OHRQoL for elderly individuals, which is approved by the previous studies. 6,11,13,40 The loss of teeth can significantly impact a person's overall well-being, both physically and emotionally. Having more natural teeth allows for better food chewing, leading to healthier and more adequate nutrition in the elderly population, ultimately increasing their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, oral health is a crucial factor that can impact an individual's quality of life, and oral healthrelated quality of life (OHRQoL) is a crucial reflection of individuals' general well-being and their overall quality of life linked to health. 10,[13][14][15][16][17] To properly evaluate the influence of oral health on an individual's overall quality of life, the Oral Health Impact Profile-14 (OHIP-14) and the Geriatric Oral Health Assessment Index-12 (GOHAI-12) are two standard questionnaires. These two are widely accepted and recognized as crucial tools for assessing oral health and its impact on a person's well-being.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Autores já concluíram que, quando do avanço da idade, a autopercepção em saúde bucal piora (Bandéca et al, 2011;Gabardo et al, 2013Gabardo et al, , 2015. Tal circunstância pode ser agravada pelo aumento de problemas bucais (Bandéca et al, 2011) e até mesmo por conta do incremento das perdas dentárias (Veeraboina, Doshi, Kulkarni, Patanapu, Dantala, & Srilatha, 2022).…”
Section: Discussionunclassified